Design and validation of a scale of motivation for scientific publication in Peruvian university professors (MoSCPU-UP) - Carranza Esteban, Renzo Felipe; Mamani-Benito, Oscar; Huancahuire-Vega, Salomón; Casildo-Bedón, Nancy; Cabrera-Orosco, Isabel; Turpo-Chaparro, Josué Edison (Frontiers in Education, 2024)
The study’s objective was to design and validate a motivation scale for scientific publication in Peruvian university professors (MoSCPU-UP). Instrumental research where a scale of 13 items distributed in 2 factors (Intentional State and Commitment-will) was designed and validated. The sample comprised 546 university professors (62.1% male) aged 22 to 67 (M = 45.05 and DS = 9.32). The sample was separated into two subgroups for the exploratory and confirmatory factor analysis. For analyzing the validity of evidence based on the content, the Aiken V coefficient was used; for construct validity, exploratory and confirmatory factor analysis was used. Reliability was studied through Cronbach’s alpha coefficient. The results show that the items received a favorable evaluation (Aiken’s V > 0.70). Goodness of fit indices were adequate (IFC = 0.93, TLI = 0.92, and RMSEA = 0.08). Likewise, the correlation between factors 1 and 2 was significant (p < 0.05). Evidence of validity based on the relationship with other variables with measures of professional self-efficacy is significant and acceptable reliability (α = 0.91; 95% CI = 0.89–0.92). In conclusion, the MoSCPU-UP scale is an instrument that reports evidence of validity and reliability.